Improvement of critical temperature of niobium nitride deposited on 8-inch silicon wafers thanks to an AlN buffer layer. (23rd February 2021) - Rhazi, Raouia; Machhadani, Houssaine; Bougerol, Catherine; Lequien, Stéphane; Robin, Eric; Rodriguez, Guillaume; Souil, Richard; Thomassin, Jean-Luc; Mollard, Nicolas; Désières, Yohan; Monroy, Eva; Olivier, Ségolène; et al.
Abstract: In this paper, we study the crystalline properties and superconducting critical temperature of ultra-thin (5–9 nm) NbN films deposited on 8-inch silicon wafers by reactive sputtering. We show that the deposition of NbN on a thin (10–20 nm) AlN buffer layer, also synthesized by reactive sputtering, improves the critical temperature by several Kelvin, up to 10 K for 9 nm NbN on 20 nm AlN. We correlate this improvement to the higher-crystalline quality of NbN on AlN. While NbN deposited directly on silicon is polycrystalline with randomly oriented grains, NbN on AlN(0001) is textured along (111), due to the close lattice match. The superconducting properties of the NbN/AlN stack are validated by the demonstration of fibre-coupled normal-incidence superconducting nanowire single photon detectors. The whole fabrication process is CMOS compatible, with a thermal budget compatible with the integration of other passive and active components on silicon. These results pave the way for the integration of a large number of surface or waveguide-integrated detectors on large-scale silicon wafers. Furthermore, as AlN is transparent over a broad wavelength range from the visible to the near-infrared, the optimized superconducting NbN/AlN stack can be used for a wide variety of applications, from imaging to quantum communications and quantum computing.